Agricultural land use management responses to a cap and trade regime for water quality in Lake Taupo catchment, New Zealand. (March 2021) - Spicer, E. Anne; Swaffield, Simon; Moore, Kevin
Highlights: Significant change to farm systems under trading but only modest land-use change. Farm system change includes deintensification and limited on-farm re-investment. Adjustments include investment outside of farming/the catchment, modifying business. Lack of viable alternative low nitrogen farming systems is a serious constraint. Underlying driving forces suggest little change in the catchment in the near future. Abstract: Managing the effects on water quality of diffuse nitrogen pollution from agriculture is a widespread problem. Cap and Trade is a policy approach which limits nitrogen discharge (the cap) but provides flexibility in land management (using trading of nitrogen). Lake Taupo Nitrogen Trading Programme (LTNTP) in New Zealand is an exemplar case in applying nitrogen discharge limits at both catchment and farm levels, with positive environmental effects at catchment scale. Less is known about the effects on land management at farm scale. This article investigates the land use and farming practice outcomes of the LTNTP. Analysis used landscape biographies focused on different scales of effect. Results identify five pathways of change in the catchment. The dominant trajectory is lowered production with little on- farm reinvestment. Lack of viable alternative low nitrogen land-uses is a major constraint, and non-financial influences on farmer trading behaviour are also significant. To achieve its socio-economic goals, Cap and Trade policy requires farmer social values aligned to cap and trade, and research that supports practice innovation.